2009
DOI: 10.1016/j.vaccine.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution of a highly attenuated recombinant vesicular stomatitis virus expressing HIV-1 Gag following intramuscular, intranasal, or intravenous inoculation

Abstract: Recombinant vesicular stomatitis viruses (rVSVs) are being developed as potential HIV-1 vaccine candidates. To characterize the in vivo replication and dissemination of rVSV vectors in mice, high doses of a highly attenuated vector expressing HIV-1 Gag, rVSV IN -N4CT9-Gag1, and a prototypic reference virus, rVSV IN -HIVGag5, were delivered intramuscularly (IM), intranasally (IN), or intravenously (IV). We used quantitative, real-time RT-PCR (Q-PCR) and standard plaque assays to measure the temporal disseminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…This contrasted sharply with the morbidity and mortality observed in animals that were inoculated the progenitor vector rVSV-G 4 (Fig.5) or the results observed in earlier studies with the VSV-Gag 4 -G 5 prototype VSV-HIV vector [24] It well known that mice are highly susceptible to VSV neuroinvasion when they are experimentally infected by IN administration or by other routes, and that susceptibility is age-dependent with young mice being prone to encephalitis; thus, rodent models have been used to study VSV neurovirulence and have been used to evaluate potential risk of using VSV vectors in [62], [89][91]. It also is known that considerable vector engineering is needed to generate genetically stable vectors that exhibit substantially reduced neurovirlence in the murine model, and that it is very difficult to completely eliminate the appearance of viral nucleic acid in the brain particularly after IN inoculation even with modified VSV that has been attenuated sufficiently to prevent symptoms [62]. Consistent with these earlier findings, rVSV-EnvG 4 -G 6 gRNA was detectable in whole brain extracts prepared from mice vaccinated by the IN route, but it is important to note that N mRNA quantities were just above the limit of detection in only 1 of 4 animals indicating that gene expression and replication in the brain was quite restricted, which was consistent with our observation of no significant weight loss, absence of fever, and no distress caused by rVSV-EnvG 4 -G 6 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasted sharply with the morbidity and mortality observed in animals that were inoculated the progenitor vector rVSV-G 4 (Fig.5) or the results observed in earlier studies with the VSV-Gag 4 -G 5 prototype VSV-HIV vector [24] It well known that mice are highly susceptible to VSV neuroinvasion when they are experimentally infected by IN administration or by other routes, and that susceptibility is age-dependent with young mice being prone to encephalitis; thus, rodent models have been used to study VSV neurovirulence and have been used to evaluate potential risk of using VSV vectors in [62], [89][91]. It also is known that considerable vector engineering is needed to generate genetically stable vectors that exhibit substantially reduced neurovirlence in the murine model, and that it is very difficult to completely eliminate the appearance of viral nucleic acid in the brain particularly after IN inoculation even with modified VSV that has been attenuated sufficiently to prevent symptoms [62]. Consistent with these earlier findings, rVSV-EnvG 4 -G 6 gRNA was detectable in whole brain extracts prepared from mice vaccinated by the IN route, but it is important to note that N mRNA quantities were just above the limit of detection in only 1 of 4 animals indicating that gene expression and replication in the brain was quite restricted, which was consistent with our observation of no significant weight loss, absence of fever, and no distress caused by rVSV-EnvG 4 -G 6 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also reported the concentration in lymph nodes and long-term persistence of rwt and other attenuated VSV vector RNAs after i.m. inoculation of mice (12).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adenovirus type 5-vectored DNA vaccine was found to be biodistributed only to spleen and liver through binding to coxsackievirus and adenovirus receptor (23). Recombinant vesicular stomatitis virus expressing HIV-1 Gag showed greater persistence in lymph nodes compared to other tissues after intramuscular administrations (24).…”
Section: Muscle Blood Thymus Ln Spleen Liver Kidney Lung Heart Brain mentioning
confidence: 99%